Evolusi Agama dan Budaya Akibat Covid-19 Ditinjau dari Pendekatan Antropologi - Handayani, Ilham Putri (Lembaga Yasin AlSys, 2022)
The recent Covid-19 pandemic has caused panic, fear, and various other exaggerated experssions among the public. This is due to differences in background, religion, education, personality and individual perceptions of society which of course are also different. The purpose of this study is to examine the concept of an anthropological approach, how the Covid-19 pandemic is examined from an anthropological perspective and what kind of new culture is formed during this pandemic. This research is a qualitative approach method to explain facts, data and research objects. This research was carried out in 3 mosques in Yogyakarta with research informants namely takmir from the 3 mosque andrsidntsasreinsformcement of the data obtained. As for the research data collected throught 3 techniques, namely observation, interviews and documentation. The result of this study indicate that evolution of religion and culture that occurred as a result of the Covid-19 pandemic in Yogyakarta, including restrictions on religion such as congregational prayers, recitations and Tabligh Akbar, have been tightened or even stopped. Likewise, the homecoming culture.